2019
DOI: 10.14710/jksa.22.3.93-98
|View full text |Cite
|
Sign up to set email alerts
|

Innovation of Carbon from Pectin Templated in Fabrication of Interlayer-free Silica-Pectin Membrane

Abstract: Water scarcity is the main issues in Indonesia especially for coastal areas. As a consequence, the water has high salinity of >50.000 ppm salt concentration where an appropriate treatment is necessary before consumed. In this case, desalination process could be carried out using inorganic silica membranes. However, during the process the pore of silica membranes were collapsed due to the directly contact of pores to water molecules for a long term performance. Thereby, in this work the innovation of membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…is a bit than 0.5 a.u.. It means functionalize of siloxane group is dominate in organosilica xerogel which the significance of producing the organosilica structure become mesopore [23]. Comparing to previous study reported [24] by of relative ratio of Si-OH/Si-O-Si surface area in this work is quiet small 50% at same calcine temperature 250 °C.…”
Section: Peak Area Ratio Of Carbon Xerogelsmentioning
confidence: 46%
“…is a bit than 0.5 a.u.. It means functionalize of siloxane group is dominate in organosilica xerogel which the significance of producing the organosilica structure become mesopore [23]. Comparing to previous study reported [24] by of relative ratio of Si-OH/Si-O-Si surface area in this work is quiet small 50% at same calcine temperature 250 °C.…”
Section: Peak Area Ratio Of Carbon Xerogelsmentioning
confidence: 46%
“…brane with great performance (Elma Muthia & Setyawan, 2018;Mujiyanti et al, 2019;Pratiwi et al, 2019a;Rampun Erdina Lulu Atika et al, 2019;Syauqiyah et al, 2019). Instead of the air, the vacuum condition in this research successfully preventing a high lost mass of organic carbon.…”
Section: Characteristic Of Organo-silica Membranementioning
confidence: 84%
“…Preparation of silica-pectin sols were conducted via sol gel method with the detail procedure can be found in our previous work reported by Pratiwi et al, [45]. The final molar ratios of silica-pectin sols of TEOS: ethanol: HNO 3 :H 2 O:NH 3 :pectin were obtained become 1:38:0.0008:5:0.0003:0.00065.…”
Section: Silica-pectin Sols Preparation and Characterizationmentioning
confidence: 99%